2023
DOI: 10.1097/gme.0000000000002144
|View full text |Cite
|
Sign up to set email alerts
|

Symptom monitoring improves physical and emotional outcomes during menopause: a randomized controlled trial

Abstract: Objectives: A recent systematic review suggested that symptom monitoring can result in reductions in menopausal symptoms and improvements in health-related behaviors. To date, no studies have experimentally investigated whether symptom monitoring could be a beneficial intervention during the menopause transition. Methods: One hundred perimenopausal and postmenopausal women (mean age, 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
5
3
0
Order By: Relevance
“…These findings remained significant after controlling for covariates such as HRT use, hormonal contraceptive use, supplement use, age, and current comorbidities. These findings are in line with prior research in the field of female health which has demonstrated that symptom monitoring during menopause and use of digital health apps which enable period logging and digital health promoting activities are associated with health improvements (5,6,3,4).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings remained significant after controlling for covariates such as HRT use, hormonal contraceptive use, supplement use, age, and current comorbidities. These findings are in line with prior research in the field of female health which has demonstrated that symptom monitoring during menopause and use of digital health apps which enable period logging and digital health promoting activities are associated with health improvements (5,6,3,4).…”
Section: Discussionsupporting
confidence: 90%
“…Of the four symptom domains evaluated, reporting psychological and cognitive symptoms at baseline was associated with the greatest reductions in symptom scores across the 2-month period. This outcome may further evidence findings from Andrews et al's (6) randomised trial, which demonstrated that a daily symptom monitoring intervention was associated with reductions in stress and anxiety, brain fog, low energy, and poor concentration, all of which were assessed as psychological and cognitive symptoms in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 1 shows menopausal symptoms and their frequency distributions in the cohort. Using the methods employed in previous research using the daily record keeping form, 6 8 symptom scores were calculated for each instance the user logged their symptoms by multiplying total number of symptoms with their average symptom severity, for example, hot flushes (severity=1), sleeping problems (severity=2), night sweats (severity=3) would result in a total symptom score of=6. A continuous symptom difference score was calculated to observe how symptoms increased or decreased throughout the 2-month app usage period.…”
Section: Methodsmentioning
confidence: 99%